2018
DOI: 10.12659/msm.906596
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Circulating miRNA-320a/b and D-Dimer Improves Diagnostic Accuracy in Deep Vein Thrombosis Patients

Abstract: BackgroundD-dimer tests have been widely used to rule-out deep venous thrombosis (DVT), but with low specificity. Circulating microRNAs (miRNAs) are novel promising biomarkers in diverse diseases. The purpose of our study was to identify the diagnostic abilities of circulating miRNA-320a/b and to assess their correlation with plasma D-dimer in DVT and post-thrombotic syndrome (PTS) patients.Material/MethodsPlasma samples were taken from 30 DVT patients, 30 PTS patients, and 30 age- and sex-matched healthy volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 40 publications
0
28
1
Order By: Relevance
“…The targeted genes, which have been validated by qPCR, western blot, or reporter assay, were summarized in a table as gene symbols (Table 4). The gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of these target genes were then performed by DAVID Bioinformatics Resources 6.8 (https://david.ncifcrf.gov/) [29, 69].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The targeted genes, which have been validated by qPCR, western blot, or reporter assay, were summarized in a table as gene symbols (Table 4). The gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of these target genes were then performed by DAVID Bioinformatics Resources 6.8 (https://david.ncifcrf.gov/) [29, 69].…”
Section: Methodsmentioning
confidence: 99%
“…However, there is only limited evidence on potentially altered circulating miRNA levels in VTE. To our knowledge, only a few studies have investigated the association between circulating miRNAs and unprovoked VTE [2529]. Wang et al found that miR-424-5p is increased in patients with acute venous thrombosis and that it is correlated with a marker of hypercoagulability (D-dimer and APC-PCI complex) [25].…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that among all miRNAs characterized in the fourteen studies described in Table 2, only six miRNAs were identified in more than one study. In the context of VTE, miR-532 [44,55], miR-320a [51,54], miR-320b [51,54], and miR-424-5p [45,54] were found to be upregulated, miR-103a-3p [52,54,55] was downregulated, and miR-27b yielded conflicting results, as it was up-and downregulated [50,55]. Several factors may account for the poor reproducibility among studies such as differences in clinical characteristics of participants, time from the occurrence of the thrombotic event to blood sampling, conditions of sample collection, sample processing (e.g., centrifugation speed and time) and storage, protocol used for RNA isolation, and methods for miRNA quantification and data normalization [20,58].…”
Section: Methodological Challenges and Future Perspectives In Epidemimentioning
confidence: 99%
“…In two other studies by Zhou et al (2016) [47] and Liu et al (2018) [48], plasma expression levels of miR-28-3p and miR-221 were shown to be upregulated in PE patients compared to healthy controls. In studies in which the expression of a specific miRNA was examined, levels of miR-26a [49] were found to be downregulated, whereas levels of miR-27a, miR-27b, miR-320a, and miR-320b were upregulated [50,51] in PE and DVT patients as described in Table 2. Table 1 for literature references).…”
Section: Epidemiological Studies: Mirnas and Venous Thromboembolismmentioning
confidence: 99%
See 1 more Smart Citation